1981
DOI: 10.1093/geronj/36.3.316
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in Processing Explicit and Implicit Language

Abstract: After reading short prose passages, older (M = 66.5 years) and younger (M = 18.3 years) adults verified the meaning of a test sentence which represented either a paraphrase or an inference from the preceding passage. There were no age differences in accuracy of verification performance with immediate testing, but older subjects made significantly more errors on a delayed test. Verification latency was longer for inference than paraphrase test sentences for both age groups, and older subjects were slower than y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0
3

Year Published

1983
1983
1997
1997

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 0 publications
3
24
0
3
Order By: Relevance
“…Furthermore, these results are in agreement with the current view that older adults are capable of using contextual information and making inferences for language processing (Belmore, 1981;Burke & Yee, 1984;Light et al, 1982;Light & Albertson, 1988;Light and Capps, 1986;Till, 1985;Zacks & Hasher, 1988;Zelinski & Miura, 1990) when the demands placed upon working memory are minimal.…”
Section: Djscussjonsupporting
confidence: 91%
“…Furthermore, these results are in agreement with the current view that older adults are capable of using contextual information and making inferences for language processing (Belmore, 1981;Burke & Yee, 1984;Light et al, 1982;Light & Albertson, 1988;Light and Capps, 1986;Till, 1985;Zacks & Hasher, 1988;Zelinski & Miura, 1990) when the demands placed upon working memory are minimal.…”
Section: Djscussjonsupporting
confidence: 91%
“…To the extent that the 'easy' sentences initiated inferential processing similar to that induced by pre vious researchers and found in most language comprehension tasks, this outcome was not surprising. However, the number of 'easy' sentences recalled was related to age level, with older adults remembering fewer such sentences than younger adults; this paralleled the results of Belmore [1981] and Light et al [1982]. Finally, age was again not related to the number of aha sentences recalled.…”
Section: Everyday Insight and Rememberingmentioning
confidence: 57%
“…In the same vein, Cohen [47] found that older subjects were less accurate than younger subjects on various measures of language comprehension for short texts, including a measure for verification of inferences. However, Belmore [13] found no significant differences between young and old subjects in ability for processing implicit or inferential language.…”
Section: Downloaded By [Universitaetsbibliothek Giessen] At 06:54 07 mentioning
confidence: 87%